A pilot study on intracerebral hemorrhage imaging based on electrical capacitance tomography - Xu, Rui; Zhuang, Wei; Bai, Zelin; Wang, Feng; Chen, Mingsheng; Liu, Nan; Jin, Gui (Frontiers in Physics, 2023)
Intracerebral hemorrhage (ICH) is a devastating disease with high rates of mortality and disability. The survival rate and postoperative outcome of ICH can be greatly improved through prompt diagnosis and treatment. CT and MRI are now the gold standards for the diagnosis of ICH, but they aren't practical for use in pre-hospital emergencies or at the bedside monitoring. Based on the earlier research of ICH detection with a single parallel plate electrode sensor, we developed a 16-electrode Electrical Capacitance Tomography (ECT) system for two-dimensional tomographic imaging of ICH in this study. A 5-layer spherical numerical model and an ex vivo porcine physical model of ICH were created for ECT simulation imaging and actual imaging, respectively, to assess the feasibility of this ECT for ICH imaging. The bleeding circles were easily seen in the image reconstruction in numerical imaging. In ex vivo imaging, the existence of bleeding was also more clearly shown with the ECT system; however, the position of the bleeding reconstructed in the image was offset by 3 mm from the real site; the study analyzes the causes of this discrepancy and discusses the steps that may be taken to rectify it. Overall, the simulation and ex vivo experimental trials validated the potential of ICH imaging with the ECT method; however, further work is required to increase the performance of the ECT and a more advanced imaging reconstruction algorithm is urgently needed for ICH imaging.